The Innovative Learning of Square and Rectangle using Macanan Traditional Indonesian Game - Padhila Angraini; Rully Charitas Indra Prahmana; Masitah Shahrill (Southeast Asian Mathematics Education Journal, 2021)
Geometry is one of the essential mathematics materials, such as square and rectangle. However, most elementary school students experience difficulty in understanding it due to the abstractness of the geometric material. Furthermore, teachers teaching in the remote areas of Indonesia still encounter problems exploring this abstract material to make students understand caused by the limited learning resources. On the other hand, students in remote areas are familiar with traditional games, such as Macanan. Hence, the objective of this study is to design learning activities utilizing Macanan game in assisting students understand the concept of the perimeter and area of squares and rectangles for fourth-grade students. A design research approach was implemented and performed at one of the elementary schools in Jambi, Indonesia. The research results presented that Macanan could be a context for a starting point in this learning design of both square and rectangular learning. Employing this context, it would be fun, enjoyable, and easy to understand the perimeter and area of squares and rectangles for students. This game could be a context for teachers in remote areas in teaching geometry and be a reference for identifying other contexts which can make mathematics learning easy in remote areas.